2019
DOI: 10.3340/jkns.2019.0061
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Circadian Variation in Ictus of Aneurysmal Subarachnoid Hemorrhage and Physical Activity

Abstract: Objective The circadian pattern of the onset time of aneurysmal subarachnoid hemorrhage (aSAH) has been reported by various authors. However, the effect of the degree of physical exertion on the circadian pattern has not been studied in detail. Therefore, we conducted this study to investigate the effect of physical exertion on the circadian pattern of aSAH. Methods Of the 335 patients presenting with aSAH from January 2012 to December 2017, 234 patients with identifiab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In this study, we identified a bimodal circadian pattern (morning peak and late afternoon peak) of aSAH onset among the Chinese population by using a nonlinear Fourier model and also performed detailed subgroup analyses to assess potential influencing factors. Some Asian studies reported similar bimodal pattern [ 3 10 36 ]. The difference in chronobiological patterns between Asians and Europeans may due to diverse social habits and dietary patterns in different cultures.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In this study, we identified a bimodal circadian pattern (morning peak and late afternoon peak) of aSAH onset among the Chinese population by using a nonlinear Fourier model and also performed detailed subgroup analyses to assess potential influencing factors. Some Asian studies reported similar bimodal pattern [ 3 10 36 ]. The difference in chronobiological patterns between Asians and Europeans may due to diverse social habits and dietary patterns in different cultures.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies of different races yielded inconsistent results on the diurnal variation of aSAH [ 3 5 6 ]. Most of them were conducted in Western countries, and they lacked subgroup analyses of influencing factors such as age, gender, and hypertension [ 5 6 7 8 9 10 11 ]. The incidence of aSAH onset could be very different among people in distinct cultures for differential lifestyle habits.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent time frame for aneurysm rupture is from 7:00 to 12:00, especially for male patients. Aneurysm ruptures often occur in the early morning and early evening, previous studies have reported the same phenomenon 16,26–28 . The potential reason for this phenomenon may be the fluctuation of systemic blood pressure.…”
Section: Discussionmentioning
confidence: 79%
“…Aneurysm ruptures often occur in the early morning and early evening, previous studies have reported the same phenomenon. 16,[26][27][28] The potential reason for this phenomenon may be the fluctuation of systemic blood pressure. It is well known that the systemic blood pressure starts to increase at 05:00-06:00 and reaches the climax at 09:00, then declines gradually at 18:00 toward a minimum at 02:00-03:00.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is connected to a transient increase of the blood pressure for a few hours and it could play an important role in the rupture of an aneurysm. A bimodal pattern of SAH occurs in the morning and the evening [10] when cigarette smoking and alcohol use usually displays its peaks.…”
Section: Discussionmentioning
confidence: 99%